Shear strengthening of T cross section reinforced concrete beams by near surface mounted technique - Dias, Salvador J. E. (2008)
With the purpose of evaluating the influence of both the percentage and inclination of the CFRP laminates on the effectiveness of the NSM technique for the shear strengthening of reinforced concrete T beams, an experimental program was carried out, using three percentages of laminates and, for each one, three inclinations: 90°, 60° and 45°. The CFRPstrengthened beams had a steel stirrup reinforcement ratio ( sw r ) of 0.1%. The highest CFRP percentage was designed to provide a maximum load similar to the one of a reference beam reinforced with sw r equal to 0.24%. Although these beams have had a similar maximum load, the beams with CFRP presented higher stiffness. Laminates at 60° was the most effective shear strengthening configuration, having provided a maximum increase in the load capacity of 33%. The contribution of the CFRP strengthening systems was limited by the concrete tensile strength. Below certain spacing between laminates, a group effect occurs due to the interference between consecutive concrete failure surfaces, leading to the detachment of “two lateral walls” from the underlying beam core.